Nutritious and delicious? A non-invasive study of food plant choices by Svalbard reindeer in Summer and late Autumn - Eikeland, Oline (UiT Norges arktiske universitet, 2023)
Seasonality affects growing patterns of vegetation and habitat use by herbivores. Short growing seasons make plants grow quickly through phenological stages which alters their nutrient levels and thus habitat use of herbivores that depend on energy assimilation in summer. Selective foraging that increases intake of high-quality forage can be highly advantageous and is usually a trade-off between forage quantity and quality. In the high Arctic, characterised by extreme seasonality, I examined 1) what plant species and plant functional groups were selected by Svalbard reindeer on a fine patch-level scale, 2) how selectivity changed from summer (when available plant biomass is at its highest) to autumn (when most plants are senescing and animals are at their fattest), and 3) how forage selectivity tied to plant nutrients and plant antiherbivore defences over the season. Svalbard reindeer displayed preference of specific plant functional groups consisting of certain key forage species, and forage selection changed throughout the study period. Selectivity was not found to be affected by concentrations of the plant nutrients nitrogen and phosphorus. Surprisingly, grazing selectivity related positively to silicon which is thought to be a herbivore deterrent in plants. Phenolics had a net negative effect on selectivity, whereas the phenolics to nitrogen ratio did not affect grazing preference in summer, and only later in the season showed a negative effect.